OsWRKY53 Promotes Abscisic Acid Accumulation to Accelerate Leaf Senescence and Inhibit Seed Germination by Downregulating Abscisic Acid Catabolic Genes in Rice - Xie, Wenya; Li, Xinru; Wang, Shiping; Yuan, Meng (Frontiers in Plant Science, 2022)
Abscisic acid (ABA) largely promotes leaf senescence and inhibits seed germination in plants. Endogenous ABA content is finely tuned by many transcription factors. Here, we show that OsWRKY53 is a positive regulator of leaf senescence and a negative regulator of seed germination in rice. OsWRKY53 expression was induced in leaves under aging, dark and ABA treatment. The OsWRKY53-overexpressing plants showed early yellowing leaves, while the oswrky53 knockout mutants maintained green leaves than the wild type under natural, dark-induced, and ABA-induced senescence conditions. Transcriptional analysis revealed that ABA catabolic genes OsABA8ox1 and OsABA8ox2, two key genes participate in ABA catabolism harboring ABA 8’-hydroxylase activity, were markedly down-regulated in OsWRKY53-overexpressing leaves. Chromatin immunoprecipitation and protoplast transient assays revealed that OsWRKY53 directly bound to the promoters of OsABA8ox1 and OsABA8ox2 to repress their transcription, resulting in elevated endogenous ABA contents which promoted premature leaf senescence in the OsWRKY53-overexpressing plants. It indicates that OsWRKY53 is a positive regulator through regulating ABA accumulation to promote leaf senescence. In addition, accumulated ABA simultaneously inhibited seed germination and post-germination growth in OsWRKY53-overexpressing plants. Taken together, OsWRKY53 suppresses the transcript of ABA catabolic genes to promote ABA accumulation to modulate ABA-induced leaf senescence and ABA-mediated inhibition of seed germination.